Contemporary Understanding of miRNA-Based Regulation of Secondary Metabolites Biosynthesis in Plants - Gupta, Om P.; Karkute, Suhas G.; Banerjee, Sagar; Meena, Nand L.; Dahuja, Anil (Frontiers in Plant Science, 2017)
Plant’s secondary metabolites such as flavonoids, terpenoids and alkaloids etc. are known for their role in the defence against various insects-pests of plants and for medicinal benefits in human. Due to the immense biological importance of these phytochemicals, understanding the regulation of their biosynthetic pathway is crucial. In the recent past, advancement in the molecular technologies has enabled us to better understand the proteins, enzymes, genes, etc. involved in the biosynthetic pathway of the secondary metabolites. miRNAs are magical, tiny, noncoding ribonucleotides that function as critical regulators of gene expression in eukaryotes. Despite the accumulated knowledge of the miRNA-mediated regulation of several processes, the involvement of miRNAs in regulating secondary plant product biosynthesis is still poorly understood. Here, we summarize the recent progress made in the area of identification and characterizations of miRNAs involved in regulating the biosynthesis of secondary metabolites in plants and discuss the future perspectives for designing the viable strategies for their targeted manipulation.